Long-term outcomes of transcatheter Potts shunt in children with suprasystemic pulmonary arterial hypertension - Haddad, Raymond N.; Levy, Maryline; Szezepanski, Isabelle; Malekzadeh-Milani, Sophie; Bonnet, Damien (Frontiers in Cardiovascular Medicine, 2022)
Background: Transcatheter Potts shunt (TPS) is a palliation alternative for children with severe pulmonary arterial hypertension (PAH). Debates on the long-term outcomes remain unsolved. Objectives: To evaluate long-term clinical and procedural outcomes of TPS intervention. Methods: Single-center retrospective data review of children with severe PAH who had TPS between 2009 and 2018. Patients who died per-operatively and early post-procedure were excluded. Long-term outcomes of survivors were evaluated. Results: Out of 13 identified patients (53.8% males), 7 had endovascular stenting of probe/patent arterial ducts, while 6 individuals had aorta-to-pulmonary radiofrequency perforation and covered stent placement. Compared to baseline, the overall clinical condition significantly improved at discharge (p<0.001) and stayed better at the last visit (p<0.05) despite frequent clinical worsening events across follow-up. Improvement in functional class across follow-up was significant (p<0.001). There was however no significant improvement in other disease markers (TPASE, 6MWD z-scores, and NT-proBNP levels) or reduction in PAH medications. The median follow-up was 77.4 months (IQR, 70.7-113.4). Survival was 100% at 1 year and 92.3% at 6 years. Freedom from reinterventions was 77% at 1 year and 21% at 6 years. Nine (69.2%) patients had stent reinterventions at a median of 25 months (IQR, 9.5-56) postoperative. Balloon dilatation and restenting were performed in 53.8% and 46.2% of patients, respectively. High-pressure post-dilatation of implanted stents during TPS intervention for incomplete stent expansion and/or residual pressure gradient was associated with higher rates of reinterventions (p=0.021). Stent malfunctioning was present in 46.2% of patients at last follow-up. Two patients are listed for heart-lung transplantation. Conclusions: Survivors of TPS procedures experience significant improvement in functional class that can be durable. Clinical worsening and stent malfunctioning are frequent morbid events indicating recurrent transcatheter reinterventions throughout follow-up. Six-year survival is however satisfactory.